Wage Incidence of Local Corporate Taxation - Micro Evidence from Germany - Andreas Peichl; Clemens Fuest; Sebastian Siegloch (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
In this paper we provide empirical evidence on the wage incidence of the German business tax, which is set at the municipal level. For our analysis, we use very rich administrative linked employer-employee panel data, covering 11 years, and link it to data on the business tax rates of about 11,100 German municipalities. On average 8% of the municipalities adjust their business tax rate per year. We are thus able to exploit multiple quasi-natural experiments to identify the tax incidence on wages. While the unique German setting allows us to gauge general equilibrium wage effects, the detailed administrative data enables us to estimate heterogeneous incidence effects and to explore different channels of how the business tax burden is passed on. Consistent with our theoretical model, we find a negative direct effect of corporate taxation on wage, arising in a collective wage bargaining context. A one euro increase in the annual tax liabilities yields a 50 cent decrease of the annual wage bill. This burden is borne high- and medium-skilled labor. Furthermore, we show that the general equilibrium effect on wages is negligible in the context of our study due to the high regional labor mobility.
Keywords: H22; H25; J30; 330